(untitled) (Al-Aasar, 2025)
This article offers an intellectual critique of Jamshed Kamboh’s poetry, discussing the theme concerns, literary features, and style aspects that define his work. Through critical examination of Jamshed Kamboh’s poems, this research reveals the poet’s distinctive viewpoint on life, love, and social matters. The article discusses how Jamshed Kamboh’s poetry portrays his experiences, emotions, and observations and how his work fits into the literary scenario of Urdu poetry. This article presents an insightful view of Jamshed Kamboh’s poetic vision, his language, and how his work influences readers. Through the analytical and creative aspects of Jamshed Kamboh’s poetry, this review attempts to highlight the importance of his work on Urdu literature.